A New Protein–Ligand Trapping System to Rapidly Screen and Discover Small-Molecule Inhibitors of PD-L1 from Natural Products - Yazhuo Huang; Senfeng Sun; Runxin Yin; Zongtao Lin; Daidong Wang; Wanwan Wang; Xiangyu Fu; Jing Wang; Xinyu Lei; Mimi Sun; Shizhong Chen; Hong Wang (Molecules)
Chinese herbal medicines have played a significant role in the development of new and effective drugs, but how to identify the active ingredients from complex extracts of traditional Chinese herbal medicines was a research difficulty. In recent years, few studies have focused on high-efficiency identification of small-molecule inhibitors of Programmed Death Ligand 1 with lower antigenicity and flexible structure tunability. In order to identify small molecule inhibitors of PD-L1 from complex Chinese herbal extracts, this study established a protein–ligand trapping system based on high-performance liquid chromatography coupled with a photo-diode array detector, ion trap/quadrupole time-of-flight tandem mass spectrometry, and a Programmed Death Ligand 1 affinity chromatography unit (ACPD-L1-HPLC-PDA-IT-TOF (Q-TOF)-MS) to rapidly screen and identify small-molecule inhibitors of Programmed Death Ligand 1 from Toddalia asiatica (L.) Lam. Fourteen components were then identified as PD-L1 binders, and surface plasmon resonance (SPR) validation results showed that six of them—magnoflorine (6), nitidine (22), chelerythrine (24), jatrorrhizine (13), toddaculin (68), and toddanol (45)—displayed PD-L1 binding activity. Laser scanning confocal microscopy results demonstrated that these compounds effectively inhibited the binding of PD-1 to PD-L1 in a dose-dependent manner. Additionally, flow cytometry analysis indicated they could promote human lung cancer cell line (A549) apoptosis when co-cultured with Peripheral Blood Mononuclear Cells (PBMCs). The system’s innovation lies in its first integration of dynamic protein–ligand trapping with multi-dimensional validation, coupled with high-throughput screening capacity for structurally diverse natural products. This workflow overcomes traditional phytochemical screening bottlenecks by preserving native protein conformations during affinity capture while maintaining chromatographic resolution, offering a transformative template for accelerating natural product-derived immunotherapeutics through the PD-1/PD-L1 pathway.